توندوتیژی دژی مێینە لە چوارچێوەی یاسا و ڕێکەوتننامە نێودەوڵەتییەکاندا: تویژینەوەیەکی تیۆری وەسفی شیکارییە - قادر, پ . د ژیا عباس; خالد, علی جعفر (Sulaimani Journal for Humanities, 2024)
Relations between family members, in this tumultuous time, should be regulated in accordance with the law, strictly legal so that it is at the service of individuals in an applied manner and regulates all relationships that connects individuals to each other, and to achieve its goal from a practical point of view, moving towards providing services for all family members to keep them from disintegration. This research entitled (Violence against Women within the framework of international laws and treaties) was written with the aim of knowing the status of women and their rights in the Iraqi laws in force as well as regional laws Kurdistan, as well as knowledge of those articles and legal paragraphs that prevent domestic violence, especially Violence against women, as several international conventions have been used, including the Universal Declaration of Rights Issued at the United Nations in 1979. CEDAW is focused on human Convention. All women's rights, in particular the right to equality in domestic legislation and the right to women's equality with men before the law and the courts, as well as the right to nationality and the rights granted to men, these rights need to be enforced, and it is the responsibility of the Member States that have agreed to them. It signed all its provisions, but this responsibility is, basically, a moral responsibility, not a legal responsibility. Legal responsibility, we see that some Middle Eastern countries, including Iraq, have not established these rights. In its internal laws in force and has not developed a mechanism for its implementation, and in return we see that the status of women in The Kurdistan region is legally better than the rest of Iraq, especially protecting them from violence. Family, where special laws were developed such as Law No. 8 of 2011, as well as the establishment of Courts and related institutions. The researcher benefited from some applicable Iraqi laws, such as the Penal Code No. 111 of the vear 1969 Amendment, we saw that domestic violence in this law was not counted crime, is not this only, but there are facilities to carry it out, as well as we find in the Personal Status Law No. 88 of the year 1959 Many gender differences Women's rights were not taken as men's rights, but then, Fortunately, laws issued by the Kurdistan Parliament, according to which these articles and paragraphs were amended, which are directed against women, especially domestic violence and the killing of women under the pretext of honor and and motivated by marital infidelity, but there is another problem, which is the non-implementation of these laws on all Kurdistan Region regions. especially in areas outside the administration of the region, where laws are still. The old Iraqi is in force and is implemented on the family in general and on women in particular, but we sometimes find that these laws, even within some regions of the region, are not implemented except proportionally.
Keywords: (توندوتیژی توندوتیژی دژی مێینە یاسا یاساکارپێکراوەکانی هەرێمی کوردستان مافەکانی مرۆڤ ڕێکەوتننامە نێودەوڵەتییەکان)